2020
DOI: 10.2460/javma.256.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for dogs with functional thyroid tumors treated by surgical excision alone

Abstract: OBJECTIVE To describe clinical findings and survival times for dogs with functional thyroid tumors treated with surgery alone and investigate potential prognostic factors for outcome in these patients. ANIMALS 27 client-owned dogs. PROCEDURES Medical records of 9 institutions were reviewed to identify dogs with hyperthyroidism secondary to thyroid neoplasia that were treated with surgery alone between 2005 and 2015. Data collected included signalment, hematologic and physical examination findings, tumor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This consideration is consistent with the prolonged survival times previously reported for surgically resected early-stage thyroid tumors and with metastases being more frequently detected during necroscopy (60-80%) than at the time of treatment (7-38%). 37,38 In the study population, at least one "hot" node was extirpated in each dog, and only 7/34 hot nodes were not blue stained, confirming the correspondence between RC and blue dye. 9,30 In human medicine adverse reactions to methylene blue injection are not rare, and some authors suggest the omission of blue dye owing the high detection rates reported with use of the radiopharmaceutical alone.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This consideration is consistent with the prolonged survival times previously reported for surgically resected early-stage thyroid tumors and with metastases being more frequently detected during necroscopy (60-80%) than at the time of treatment (7-38%). 37,38 In the study population, at least one "hot" node was extirpated in each dog, and only 7/34 hot nodes were not blue stained, confirming the correspondence between RC and blue dye. 9,30 In human medicine adverse reactions to methylene blue injection are not rare, and some authors suggest the omission of blue dye owing the high detection rates reported with use of the radiopharmaceutical alone.…”
Section: Discussionmentioning
confidence: 55%
“…Reported rates of nodal metastases for thyroid carcinomas varies significantly among studies (7%-38%), probably due to the lack of standardization in staging modalities and inclusion of early to advance stage tumours. [36][37][38] Recently, metastases to surgically excised deep cervical lymph nodes have been described in 45% of dogs with thyroid carcinoma, several of which had negative prognostic factors such has bilateral tumours, lymphatic or vascular invasion and capsular invasion. 39 Conversely, the four thyroid tumours included in the present study were early-stage and no negative prognostic factors were recognized, except for the ectopic location of one thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…2,[6][7][8] Surgical excision is the treatment of choice for non-metastatic, mobile tumours; however, only approximately 25%-50% of cases are amenable to surgery, due to large tumour size and fixation to underlying tissues. 5,[9][10][11] Treatment with external beam radiation therapy (RT) has been reported for non-resectable, advanced stage thyroid carcinomas. 9,[12][13][14] Medical treatment for non-resectable tumours using platinum-based chemotherapy or doxorubicin results in variable outcomes, with 30%-50% tumours showing some response.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical excision is the treatment of choice for non‐metastatic, mobile tumours; however, only approximately 25%–50% of cases are amenable to surgery, due to large tumour size and fixation to underlying tissues 5,9–11 . Treatment with external beam radiation therapy (RT) has been reported for non‐resectable, advanced stage thyroid carcinomas 9,12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Thyroid adenocarcinomas are considered malignant and have historically represented most of the thyroid neoplasms in domestic canines, but a few cases have been documented in nondomestic cats, a bald eagle, and transgenic mice. [3][4][5][6][7] No known reports of clinical management with oral chemotherapeutic agents in nonhuman primates have been published. Many chemotherapeutic agents require intravenous administration, which can be challenging to administer in callitrichid species without anesthesia.…”
mentioning
confidence: 99%